Constitutionalism and Human Rights - Khanna, Purnima (University of Jember, 2022)
The movement for decriminalizing homosexual relations and the human rights of the LGBT community has gained momentum in the last decade. In India, various NGOs and LGBT society have fought a long battle demanding the decriminalization of homosexuality and declaring sexual orientation as part of the fundamental right to life under Article 21 of the Indian Constitution. This paper explored the Indian legislative framework dealing with transgender people. Furthermore, it extensively covered the landmark judgments delivered by the Indian judiciary on the subject matter and highlighted that these judgments had played an essential role in uplifting the cause and protecting the fundamental rights of transgenders. Using doctrinal research as its methodology, this study showed that the Indian Constitution essentially provides a fundamental right to equality under Article 14, whereas Articles 15 and 16 outline that no one shall be discriminated on the ground of sex. Also, the Indian judiciary had decriminalized Section 377 of the Indian Penal Code, considered as part of landmark judgments that recognize transgender people as a third gender. India also enacted the Transgender Protection Act 2019 to ensure the rights of transgenders. However, this Act failed to address the issue of forced sex-reassignment surgeries, which had been imposed upon transgender people against their consent. On the other hand, while transgenders are legally protected, gaining acceptance from society is another arduous task in which transgenders have struggled to realize an all-inclusive and non-judgmental environment towards persons with different sexual orientations.Keywords: Constitutionalism, Human Rights, Transgenders.